CONSTRUCTION OF THE ELECTION SUPERVISORY AGENCY AS AN EFFECTIVE ELECTION LAW ENFORCEMENT AGENCY - Zainuddin Zainuddin (NOMOI Law Review, 2022)
Law enforcerment agency in election law is always problematics all the time. The urgency to expand Bawaslu's authority in conducting supervision of elections should not only be limited to administrative matters, but needs to be considered in the process of enforcing election law, limiting the time to 7 days in reporting and 14 days in handling post-indications of fraud that occurs in the election process becomes obstacles and obstacles. The method used in this paper is normative juridical legal research. The result are Bawaslu is not only as a maker of reports and recommendations to institutions that are authorized to handle criminal and administrative violations, and not as an institution that actually has a special authority that is in the realm of election law enforcement. Thus, Bawaslu is very urgent to transform so that his authority is strengthened in the process of enforcing electoral law for criminal and administrative violations.Keywords: Law Enforcement, Election, Agency.